Highly Efficient Electrocatalytic Carboxylation of 1-Phenylethyl Chloride at Cu Foam Cathode - Wu, La-Xia; Sun, Qi-Long; Yang, Man-Ping; Zhao, Ying-Guo; Guan, Ye-Bin; Wang, Huan; Lu, Jia-Xing (Catalysts, 2018)
A simple and efficient electrocatalytic carboxylation of benzyl chloride with CO2 is described. The reaction operates under 1 atm CO2 and room temperature in an undivided cell with Cu foam cathode and Mg sacrificial anode without any additional catalyst. For the model compound 1-phenylethyl chloride, the influence of cathode material, solvent, charge, current density and temperature were investigated. Under optimized conditions, 99% yield of 2-phenylpropionic acid could be obtained. Moreover, reasonable yields were also achieved with other benzyl chlorides.